Интерактивное управление синтезом зубчатых передач - Воронцов, Б. С. (НТУ "ХПИ", 2005)
Розглядається керований комп'ютерний синтез зубчастих передач. Аналізуються різні методи створення апарату керування кривою. Приведені результати використання керованого синтезу вихідного контуру твірної поверхні.

Controlled synthesis of gear has been investigated. Different methods of creation of apparatus for the curve control have been analyzed. The results of the use of the controlled synthesis of the original profile of the forming surface have been presented.
Keywords: эвольвентное зацепление; динамические нагрузки; контактная прочность; зацепления Новикова